PRIORITISING SOIL QUALITY ASSESSMENT THROUGH THE SCREENING OF SITES: THE USE OF PUBLICLY COLLECTED DATA. (26th January 2012) - Bone, J.; Barraclough, D.; Eggleton, P.; Head, M.; Jones, D. T.; Voulvoulis, N.
ABSTRACT Emergence of policies dealing with concern over soil degradation and anthropogenic impacts to soil is likely to increase the requirement for assessment of soil quality and identification of soils at risk from degradation. An example is the proposed EU Soil Framework Directive, which features the identification of areas requiring protection from soil degradation. There have been some serious objections to such requirements on the grounds of resource and capital demands. To help to address these concerns, this work proposes a strategic set of indicators based on measured soil quality indicators. These can be used in screening locations to assess the likelihood of degradation and indicate areas for further detailed assessment. This will allow further emphasis to be placed on a smaller number of locations, which could lead to cost and resource efficiencies. Indicators have been used in the past in assessment of soil quality; they are parameters which can be measured and correspond to assessment criteria to measure and help monitor the status and changes. The study reviews the current state of soil quality assessment including methods and indicators that are used to collect data and approaches used to assess data to determine areas subject to soil degradation. Methods and practicalities for data collection and screening are discussed, including the need for further pilot testing and protocol development. Use of public data collection could allow more resource efficient protection of soils, in addition to benefits of public engagement, and raising awareness of the importance of soils and soil biodiversity. Copyright © 2012 John Wiley & Sons, Ltd.